Assess the feasibility of flipped classroom pedagogy in undergraduate nursing education in Sri Lanka: A mixed-methods study. - Punithalingam Youhasan; Yan Chen; Mataroria Lyndon; Marcus A Henning (PLoS ONE, 2021)
Background The nursing education system has evolved with an increased emphasis on student-centred education, such as implementing flipped classroom pedagogy. Given the promising positive educational outcomes, the trend of using flipped classroom pedagogy has become increasingly popular in undergraduate nursing education. However, little is known about how these flipped classroom methods impact on nursing educational practices in limited-resource settings situated in South Asia. Objective To assess the feasibility of implementing flipped classroom pedagogy in undergraduate nursing education from the nursing students' perspective. Methods This mixed-methods study employed a quantitative survey and six focus group discussions conducted in three state universities in Sri Lanka. The Nursing Students' Readiness for Flipped Classroom (NSR-FC) questionnaire was used to collect quantitative data. The semi-structured focus group discussions were conducted by using 18 reflective and open-ended questions. Descriptive statistics and multivariate analysis of variance methods were employed when analysing quantitative data. An inductive thematic analysis approach was used to summarize the focus group discussions. Results The questionnaire survey revealed that nursing students reported high levels of personal, technical, and pedagogical readiness across all three universities, while environmental readiness was perceived as low. The inductive thematic analysis identified three themes, namely: enablers, challenges, and benefits. Specifically, nursing students valued the student-centred approach. They were ready to utilize their own devices to overcome limited technological provision; however, a short training session about how to engage in the flipped classroom was desirable. Also, their exposure to basic educational technology was perceived as adequate and they were aware of the positive outcomes of flipped classroom pedagogy. Conclusion Nursing students were ready to enrol in a flipped classroom programme. The provision of technological resources in the education environment was identified as a great challenge for flipped classroom implementation. Overall, the findings indicate there are promising feasibilities for the flipped classroom implementation.